Different expression patterns of genes from the exo-xis region of bacteriophage λ and Shiga toxin-converting bacteriophage Ф24B following infection or prophage induction in Escherichia coli. - Sylwia Bloch (Public Library of Science (PLoS), 2014)
Lambdoid bacteriophages serve as useful models in microbiological and molecular studies on basic biological process. Moreover, this family of viruses plays an important role in pathogenesis of enterohemorrhagic Escherichia coli (EHEC) strains, as they are carriers of genes coding for Shiga toxins. Efficient expression of these genes requires lambdoid prophage induction and multiplication of the phage genome. Therefore, understanding the mechanisms regulating these processes appears essential for both basic knowledge and potential anti-EHEC applications. The exo-xis region, present in genomes of lambdoid bacteriophages, contains highly conserved genes of largely unknown functions. Recent report indicated that the Ea8.5 protein, encoded in this region, contains a newly discovered fused homeodomain/zinc-finger fold, suggesting its plausible regulatory role. Moreover, subsequent studies demonstrated that overexpression of the exo-xis region from a multicopy plasmid resulted in impaired lysogenization of E. coli and more effective induction of λ and Ф24B prophages. In this report, we demonstrate that after prophage induction, the increase in phage DNA content in the host cells is more efficient in E. coli bearing additional copies of the exo-xis region, while survival rate of such bacteria is lower, which corroborated previous observations. Importantly, by using quantitative real-time reverse transcription PCR, we have determined patterns of expressions of particular genes from this region. Unexpectedly, in both phages λ and Ф24B, these patterns were significantly different not only between conditions of the host cells infection by bacteriophages and prophage induction, but also between induction of prophages with various agents (mitomycin C and hydrogen peroxide). This may shed a new light on our understanding of regulation of lambdoid phage development, depending on the mode of lytic cycle initiation.